Men’s relationship to patriarchy reflections on masculinity and role models - Hentschel, Till (Revista Colombiana de Ciencias Sociales, 2024)
In today’s patriarchal and capitalist society, issues such as feminism and patriarchy are often seen as “women’s issues” and the role of women is often discussed, while men’s relationship to patriarchy is often neglected. Yet, this is a very important aspect if we want to describe the system we live in holistically. But what is men’s relationship to patriarchy?